Fluorescence quantum yield of Yb3+-doped tellurite glasses determined by thermal lens spectroscopy - Lima, S. M.; Souza, A. K. R.; Langaro, A. P.; Silva, J. R.; Costa, F. B. [UNESP]; Moraes, J. C. S. [UNESP]; Figueiredo, M. S.; Santos, F. A.; Baesso, M. L.; Nunes, L. A. O.; Andrade, L. H. C. (Elsevier B.V., 2017)
In this work, the combination of three different thermal lens spectroscopic methodologies was used to better determine the fluorescence quantum yield and to observe the concentration quenching in Yb3+-doped binary tellurite glasses (in mol%, 80TeO(2) 20Li(2)O and 80TeO(2) - 20WO(3)). The samples were synthesized by the conventional melt-quenching method and then studied using optical spectroscopy and thermal lens spectroscopy (Us). These characterizations enabled investigation of the radiative and nonradiative processes involved in the ytterbium doped systems. High fluorescence quantum yield was obtained for low Yb3+ doping (>90%), and in both glasses the Yb3+ presented concentration quenching mainly caused by impurities, host-ion interaction and OH- vibrations. The observations suggested that there is a possibility of doping the glasses with higher Yb concentration (>1.6 x 1021 ions/cm(3)) with low reduction of the quantum yield. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Fluorescence quantum yield; Ytterbium doped tellurite glasses; Optical spectroscopy; Thermal lens spectroscopy